Power Line Communication: análise da viabilidade e desempenho técnico do padrão G3-PLC para o monitoramento de variáveis em ambiente industrial - Farias, Luiz da Rocha (2017)
This work presents an analysis of the narrowband communication through the power line (PLC) in an industrial environment. For analysis, a development kit for PLCbased applications according to the G3-PLC standard was used. Experimental tests and results for different scenarios that simulate various situations existing in an industrial environment. An influence of the insertion of noise in the PLC channel is demonstrated by the drive of inverters and motors, in order to verify a nonperformance influence of the PLC communication. As a comparative basis, a maximum standard transmission distance of the AS-Interface network was used, very widespread in industrial environments. Recommendations regarding the modulation technique and the size of the data packet are presented. As a final result, it is concluded that the G3-PLC communication standard and its ROBO modulation technique meet the requirements of industrial communication, especially for industrial variable monitoring applications where time is not critical.